2012
DOI: 10.1007/s00442-012-2299-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential effectiveness of novel and old legume–rhizobia mutualisms: implications for invasion by exotic legumes

Abstract: The degree of specialization in the legume-rhizobium mutualism and the variation in the response to different potential symbionts are crucial factors for understanding the process of invasion by exotic legumes and the consequences for the native resident plants and bacteria. The enhanced novel mutualism hypothesis predicts that exotic invasive legumes would take advantage of native rhizobia present in the invaded soils. However, recent studies have shown that exotic legumes might become invasive by using exoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 38 publications
0
55
0
2
Order By: Relevance
“…Most show high levels of nodulation in invaded ranges, indicating either that effective rhizobia are widely distributed between continents and/or that many legumes can nodulate with a wide range of rhizobia strains (Rodríguez-Echeverría et al 2011, Ndlovu et al 2013. For some invasive legumes, however, novel mutualisms appear to be less effective in terms of nodulation, nitrogenase activity, and plant growth than the interactions of plants and bacteria of the same origin (Rodríguez-Echeverría et al 2012). Other studies have shown that alien legumes may become invasive by using alien microsymbionts (Rodríguez-Echeverría 2010).…”
Section: Mutualisms Enhancing Plant Invasionsmentioning
confidence: 92%
“…Most show high levels of nodulation in invaded ranges, indicating either that effective rhizobia are widely distributed between continents and/or that many legumes can nodulate with a wide range of rhizobia strains (Rodríguez-Echeverría et al 2011, Ndlovu et al 2013. For some invasive legumes, however, novel mutualisms appear to be less effective in terms of nodulation, nitrogenase activity, and plant growth than the interactions of plants and bacteria of the same origin (Rodríguez-Echeverría et al 2012). Other studies have shown that alien legumes may become invasive by using alien microsymbionts (Rodríguez-Echeverría 2010).…”
Section: Mutualisms Enhancing Plant Invasionsmentioning
confidence: 92%
“…Previous studies have implicated Bradyrhizobium strains in supporting exotic legume invasions in New Zealand (Weir et al 2004), Australia (Lafay and Burdon 2006), Africa (Boukhatem et al 2012;Ndlovu et al 2013 Boukhatem et al 2012). Finally, there are a number of reports of co-invasion by exotic legumes and their associated Bradyrhizobium bacteria (Lafay and Burdon 2006;Leary et al 2006;Rodriguez-Echeverria 2010;Rodriguez-Echeverria et al 2012). In conjunction with the widespread reports of Bradyrhizobium associations with plant invasions, the large asymmetry Bradyrhizobium-associated plant growth for invasive and native Lespedeza reported here makes Bradyrhizobium a likely candidate genus for further study in regards to L. cuneata invasion.…”
Section: Asymmetrical Benefit Of Microbial Mutualists To Native and Imentioning
confidence: 98%
“…It would be very interesting to know if the disproportionate benefits of L. cuneata reported here extend to these other kinds of symbioses. Different strains of microbial symbionts can have differential fitness effects on different plant hosts (Cardinale et al 2008;Helgason et al 2002;Rangin et al 2008;Rincon-Rosales et al 2009;RodriguezEcheverria et al 2012;van der Heijden et al 1998), and these differential effects may be related to the degree of "familiarity" between the host and the symbiont (Klironomos 2003;Rodriguez-Echeverria 2010;Rodriguez-Echeverria et al 2012). For example, in a Mediterranean dune system, the legume-rhizobium symbiosis leads to higher nodulation rates, nitrogenase activity, and plant growth when native legumes are paired with native rhizobacteria and when exotic legumes are paired with rhizobacteria from their home range (Rodriguez-Echeverria et al 2012;Thrall et al 2007).…”
Section: Asymmetrical Benefit Of Microbial Mutualists To Native and Imentioning
confidence: 99%
See 1 more Smart Citation
“…Using novel mutualisms as model systems to better understand how species enter and establish in communities may help advance basic research and fill current understanding gaps. Because they are widespread and dynamic, novel mutualisms are promising focal points for a diversity of outstanding basic questions (Table 1), and such work may build on the strong foundation in novel mutualism research established by scientists working to understand the importance of positive interactions in a context of biological invasions (e.g., Richardson et al 2000;Klironomos 2003;Ness 2003;Traveset and Richardson 2006;Aizen et al 2008;Kaiser-Bunbury et al 2011;Rodríguez-Echeverría et. al.…”
Section: Tackling New Questions and New Systems With Novel Mutualism mentioning
confidence: 99%